Combined PI3Kα-mTOR Targeting of Glioma Stem Cells - Frank D. Eckerdt (Nature Portfolio, 2020)
Abstract Glioblastoma (GBM) is the most common and lethal primary intrinsic tumour of the adult brain and evidence indicates disease progression is driven by glioma stem cells (GSCs). Extensive advances in the molecular characterization of GBM allowed classification into proneural, mesenchymal and classical subtypes, and have raised expectations these insights may predict response to targeted therapies. We utilized GBM neurospheres that display GSC characteristics and found activation of the PI3K/AKT pathway in sphere-forming cells. The PI3Kα selective inhibitor alpelisib blocked PI3K/AKT activation and inhibited spheroid growth, suggesting an essential role for the PI3Kα catalytic isoform. p110α expression was highest in the proneural subtype and this was associated with increased phosphorylation of AKT. Further, employing the GBM BioDP, we found co-expression of PIK3CA with the neuronal stem/progenitor marker NES was associated with poor prognosis in PN GBM patients, indicating a unique role for PI3Kα in PN GSCs. Alpelisib inhibited GSC neurosphere growth and these effects were more pronounced in GSCs of the PN subtype. The antineoplastic effects of alpelisib were substantially enhanced when combined with pharmacologic mTOR inhibition. These findings identify the alpha catalytic PI3K isoform as a unique therapeutic target in proneural GBM and suggest that pharmacological mTOR inhibition may sensitize GSCs to selective PI3Kα inhibition.